Two Faces of TGF-Beta1 in Breast Cancer - Joanna Magdalena Zarzynska (Hindawi Limited, 2014)
Breast cancer (BC) is potentially life-threatening malignancy that still causes high mortality among women. Scientific research in this field is focused on deeper understanding of pathogenesis and progressing of BC, in order to develop relevant diagnosis and improve therapeutic treatment. Multifunctional cytokine TGF-β1 is one of many factors that have a direct influence on BC pathophysiology. Expression of TGF-β1, induction of canonical and noncanonical signaling pathways, and mutations in genes encoding TGF-β1 and its receptors are correlated with oncogenic activity of this cytokine. In early stages of BC this cytokine inhibits epithelial cell cycle progression and promotes apoptosis, showing tumor suppressive effects. However, in late stages, TGF-β1 is linked with increased tumor progression, higher cell motility, cancer invasiveness, and metastasis. It is also involved in cancer microenvironment modification and promotion of epithelial to mesenchymal transition (EMT). This review summarizes the current knowledge on the phenomenon called "TGF-β1 paradox", showing that better understanding of TGF-β1 functions can be a step towards development of new therapeutic approaches. According to current knowledge several drugs against TGF-β1 have been developed and are either in nonclinical or in early stages of clinical investigation.